Assessment of Oral Health on Quality of Life among the Institutionalized Elderly Population of Mathura-Uttar Pradesh - Kuldeep Dhanker; Alankrita Chaudhary; Navin Anand Ingle; Navpreet Kaur (Wolters Kluwer Medknow Publications, 2013)
Objective: To assess the impact of oral health on quality of life among the institutionalized elderly population of Mathura-Uttar Pradesh. Materials and Method : A cross-sectional study comprised a sample of 302 institutionalized people over the age of 60 years. The Om1 Health Impact Profile (Oil lP) -14 was administered in structured interview format and socio-demographic information was collected prior to a clinical, oral examination. The clinical examination was conducted in order to assess the oral conditions of the participants based on the WHO criteria with other variables including wasting disease and tooth mobility. A chi square analysis and analysis of variance test with p <0.05 was performed Results: The study revealed that 17% elders were completely edentulous and 69.5% were partially edentulous. Statistically significant difference was found for oral health impact score between males and females. The overall OHIP score was found to be 69% and OHIP mean score of elders with missing and mobile teeth also showed statistically significant difference. Conclusions: Tooth loss and tooth mobility have a great impact on one's life and are strongly associated with oral health related quality of life.